Religiosity And Child Sexual Abuse: Systematic Literature Review Using Big Data with VOS Viewer Visualization - Munawaroh, Munawaroh; Farida, Ika Andrini; Hanurawan, Fattah (Kuras Institute, 2024)
Sexual harassment is a crime that is condemned worldwide due to its negative impact. Both religions and state constitutions strictly prohibit sexual abuse. One of the most common cases of sexual abuse in Indonesia is pedophilia. This study aims to determine factors that can reduce sexual harassment behavior, the impact of sexual harassment and factors that can restore victims after experiencing sexual harassment. The research method used in writing the article is a Big Data-based systematic literature review with VOS Viewer visualization by searching for published articles according to the topic published by Google Scholar and Scopus for the last 6 years (2018-2024) with the keyword “Sexual harassment”, “Religiosity”, “Children”, “Child Sexual Abuse” and